RSM-Based Analysis and Optimization Approach for Chemical Processes - Jia, Bi jue (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
This research addressed a convenient analysis and optimization approach for chemical process based on software simulation, Response Surface Methodology (RSM) and the mathematical software Matlab simultaneously. A case study of CO2 dehydration was used to showcase the capabilities of the model. In this paper, the objective of the model was to analyze the separate effects and interaction effects of factors to total energy cost of the CO2 dehydration process, and obtain explicit formulae between independent parameters and response values. With Matlab, the minimum energy onsumption was determined by optimization of parameter setting.